2002
DOI: 10.1046/j.1440-6047.11.s.7.10.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol‐enriched extract of oil palm fronds (Elaeis guineensis) promotes vascular relaxation via endothelium‐dependent mechanisms

Abstract: Plant-based polyphenolic compounds have been reported to possess cardiovascular health benefits. Several dietary sources, including herbs and spices, fruits and vegetables, and tea and wine, contain an array of biologically active compounds that have been shown to be effective in retarding oxidation of low-density lipoproteins (LDL) and promoting vascular relaxation. In the present study four different plant sources, both edible and non-edible, were evaluated for potential activity. Organic extracts enriched i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Other studies demonstrate that ferulic acids alleviates lipid peroxidation in diabetic rats, synergistically interact with other antioxidants to preserve physiological integrity of cells exposed to free radicals (Mathew and Abraham, 2004;Graf, 1992;Anselmi, 2004) and attenuates the processes that drive the pathology associated with Alzheimer's disease if the treatment is initiated before the neuroinflammatory processes can develop. In addition, ferulic acid protects against hydroxyl and peroxyl radical oxidation in synaptosomal and neuronal cell culture systems, as well as strongly inhibits arylamine N-acetyltransferase activities in human gastrointestinal microflora (Mathew and Abraham 2004;Graf, 1992;Anselmi, 2004) In conclusion, palm oil contains a rich mixture of phenolic compounds with potent antioxidant and radical scavenging activity to suggest that the widely reported capacity of palm oil to modulate the effect of oxidative stress on serum and antioxidant enzymes in membranes of liver and kidney, oxidative stress hypertension, suppress pre-neoplastic mammary epithelial cell proliferation, inhibit diesel-exhaust induced lung tumorigenesis, inhibit tumour promotion as well as modulate the immune system (Wattanapenpaiboon and Wahlqvist, 2003;Edem, 2002;Elson,1992;Sundram et al, 2003;Abeywardena et al, 2002;Balasundram et al, 2003;Yun et al, 2008) cannot be ascribed to their carotenoids and tocopherol components alone, but also to their antioxidant polyphenol contents. 祃 Methanol Extract (10g/2.5ml) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies demonstrate that ferulic acids alleviates lipid peroxidation in diabetic rats, synergistically interact with other antioxidants to preserve physiological integrity of cells exposed to free radicals (Mathew and Abraham, 2004;Graf, 1992;Anselmi, 2004) and attenuates the processes that drive the pathology associated with Alzheimer's disease if the treatment is initiated before the neuroinflammatory processes can develop. In addition, ferulic acid protects against hydroxyl and peroxyl radical oxidation in synaptosomal and neuronal cell culture systems, as well as strongly inhibits arylamine N-acetyltransferase activities in human gastrointestinal microflora (Mathew and Abraham 2004;Graf, 1992;Anselmi, 2004) In conclusion, palm oil contains a rich mixture of phenolic compounds with potent antioxidant and radical scavenging activity to suggest that the widely reported capacity of palm oil to modulate the effect of oxidative stress on serum and antioxidant enzymes in membranes of liver and kidney, oxidative stress hypertension, suppress pre-neoplastic mammary epithelial cell proliferation, inhibit diesel-exhaust induced lung tumorigenesis, inhibit tumour promotion as well as modulate the immune system (Wattanapenpaiboon and Wahlqvist, 2003;Edem, 2002;Elson,1992;Sundram et al, 2003;Abeywardena et al, 2002;Balasundram et al, 2003;Yun et al, 2008) cannot be ascribed to their carotenoids and tocopherol components alone, but also to their antioxidant polyphenol contents. 祃 Methanol Extract (10g/2.5ml) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…The fruit also contains components such as carotenoids (alpha, beta, and gamma carotenes), vitamin E (tocophoreols and tocotrienols), sterols (sitosterol, stigmasterol and campesterol), phospholipids, glycolipids and squalene, which are of known nutritional and health benefits (Wattanapenpaiboon and Wahlqvist, 2003;Manorama and Rukmini (1991). In addition, it has been reported that certain powerful water-soluble antioxidants, phenolic acids and flavonoids can be recovered from the palm oil mill effluents (Abeywardena et al, 2002;Balasundram et al, 2003;Yun et al, 2008).…”
mentioning
confidence: 99%
“…Some researchers also discovered oil palm leaves have potential health benefits. Abeywardena et al (2002) disclosed a polyphenol-enriched extract derived from Elaeis guineensis leaf. They reported that the said extract can be used to promote vascular relaxation via endothelium-dependent mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Common banana Musaceae Flower Antioxidant [139][140][141] Psidium guajava L. Guava Myrtaceae Fruit Antioxidant [142,143] Capsicum frutescens L. Bird chili Solanaceae Fruit Antioxidant, LDLr [99,100,104,107,112] modulation effects and vasorelaxation properties Lycium chinense Mill.…”
Section: Sesbania Grandifoliamentioning
confidence: 99%
“…African oil palm Arecaceae Frond Antioxidant, [104,107] vasorelaxation properties and LDLr* modulation effects Var. radiata plant NO** inhibitory Diplazium esculentum Swartz Vegetable fern Athyriaceae Shoot Antioxidant [99,100,108,109] (Retzius) Brassica alboglabra Bailey Chinese kale Brassicaceae leaves Antioxidant [99,100,110] Brassica oleracea L. Cauliflower, Broccoli, Cabbage Brassicaceae Flower leaves Antioxidant [100] and Chinese cabbage Raphanus sativus L.…”
Section: Introductionmentioning
confidence: 99%